Salt and temperature CTD data in Kattegat during 2005 and 2006 - Björk, Göran (University of Gothenburg, 2019)
In 2005 and 2006, planktonic egg surveys were conducted in February and March during the peak spawning period for Kattegat cod. The total survey period encompassed five weeks with a five-day long survey carried out every second week. During each survey 50 stations were sampled. Salinity and temperature profiles were measured by CTD (Conductivity,Temperature and Depth profiler, SBE 911plus).

The data was collected using the CTD (SBE 911plus) on board the University of Gothenburg research vessel Skagerack. The sensors on this instrument are calibrated on a routine and regular basis which ensures a good data quality.

For more information about the dataset see:
Pacariz, S., Björk, G., Jonsson, P., Börjesson, P., and Svedäng, H. A model study of the large-scale transport of fish eggs in the Kattegat in relation to egg density (2013). – ICES Journal of Marine Science, doi.10.1093/icesjms/fst144.

Under februari och mars, 2005 och 2006, genomfördes planktoniska äggundersökningar under toppen av lekperioden för Kattegattorsk. Den totala undersökningsperioden omfattade fem veckor med en fem dagar lång undersökning som genomfördes varannan vecka. Varje undersökning samlade in data från 50 stationer. Salt- och temperaturprofiler mättes med CTD (konduktivitet, temperatur och djupprofil, SBE 911plus).

Data har samlats in med hjälp av CTD (SBE 911plus) ombord på forskningsfartyget Skagerack vid Göteborgs universitet. Sensorerna på detta instrument kalibreras rutinmässigt och regelbundet vilket säkerställer en god datakvalitet.

För mer information om dataset se:
Pacariz, S., Björk, G., Jonsson, P., Börjesson, P., and Svedäng, H. A model study of the large-scale transport of fish eggs in the Kattegat in relation to egg density (2013). - ICES Journal of Marine Science, doi.10.1093/icesjms/fst144.
CTD-data för salt och temperatur i Kattegat under 2005 och 2006
Keywords: SALINITY; CONDUCTIVITY; DENSITY; WATER TEMPERATURE; ocean temperature; salt content; salthalt; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Environment; Miljö; Inland Waters; Sjöar och vattendrag